GC-MS PROFILING AND In vitro ANTIBACTERIAL EFFICACY OF AQUEOUS LEAF EXTRACTS OF Ocimum gratissimum Linn. AND Vernonia amygdalina Del - Akinjogunla, Olajide J.; Itah, A. Y. (FUDMA JOURNAL OF SCIENCES, 2024)
The increasing spread, persistence, and prevalence of multidrug-resistant bacterial strains has become a significant global public health challenge, necessitating the need for novel, potent, and alternative antimicrobial agents, particularly from medicinal plants. The study determined the bioactive phytochemical constituents and antibacterial activities of the aqueous leaf extracts of Vernonia amygdalina (ALEVA) and Ocimum gratissimum (ALEOG). In ALEVA using the agar-well diffusion method. The ALEVA contained 35 identified compounds, with cis-thujopsene (20.99%), acetic acid (20.77%), and butanoic acid, 2-methyl (12.87%) being the most abundant. Ethosuximide and cyclohexane, 1, 3-butadienylidene were detected in small amounts. The ALEOG had 44 compounds, with butanoic acid, 3-methyl (13.89%), thymol (12.43%), and butanoic acid, 2-methyl (7.22%) in the highest concentrations, while 1H-cyclopenta[a] pentalen-7-ol and 9-octadecynoic acid methyl ester were present in small amounts. The ALEOG and ALEVA showed significant (p < 0.05) inhibition at 40 mg/mL against Helicobacter pylori and other bacterial isolates, with a highest mean (x S.D.) inhibition zone diameter of 17.5 0.5 mm and 18.2 1.1 mm, respectively. The minimum inhibitory concentrations (MIC) values of ALEVA and ALEOG for the isolates ranged between 5 g/mL and 40 g/mL; the minimum bactericidal concentrations (MBC) values of ALEVA and ALEOG for the isolates ranged between 5 g/mL and 80 g/mL, with an MBC/MIC of 4. The study has demonstrated that aqueous leaf extracts from O. gratissimum and V. amygdalina possess significant antibacterial activity, supporting their traditional medicinal uses.